Life Style Patterns and its Association with Menstrual Problems among Saudi Students in Eastern Province - Najwa K. Karout (Journal of King Abdulaziz University: Medical Sciences, 2023)
This paper aims to evaluate the lifestyle of young Saudi women and to examine any association between eating habits, exercise and smoking tobacco with diff erent menstrual dysfunctions. A cross-sectional/correlational survey was conducted on a sample of 412 students from the nursing college in Al Khobar in the Eastern province. The data was collected using a self-administered questionnaire relating to menstrual problems and lifestyle patterns and revealed that an unhealthy lifestyle was common among young Saudi women and was a major concern for public health specialists. Analysis of the data also showed that eating fast food increased the risk of premenstrual syndrome, dysmenorrhea and amenorrhea. Smoking had a significant association with premenstrual syndrome and hypermenorrhea; skipping breakfast had an inverse association with amenorrhea. However, the current study did not fi nd any signifi cant association between doing exercise and menstrual disorders. In conclusion, a new trend of lifestyle in Saudi culture needs to be assessed deeply, programs for health promotion are highly recommended, and additional related studies are needed.